SCIENCE IN THE PROGRAM OF THE ELEMENTARY SCHOOL. - Avery, Lewis B. (Science Education, 1934)
The article comments on the science curriculum in elementary schools in the U.S. Science and social studies are fundamental for they furnish firsthand experiences. Other subjects become interpreters of these experiences and weave them into an understanding personality. The tentative course of study in elementary science developed in the Horace Mann Elementary School of Teachers College contributes with regard to the definition and function of elementary-school science. The combined fields of social subjects and science thus furnish the opportunity for the first-hand experiences, the interpretation of which provides educational growth and the other subjects of the curriculum are engaged in their interpretation.